(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
Several factors hinder the opening of new companies in Villavicencio and their consolidation in the market for more than five years. This increases the rates of unemployment, poverty, and inequality. From there, it is intended to design a strategic plan that increases the probability of subsistence of current and future ventures in Villavicencio, through a census-type study, applied under a survey model to 257 companies in the commercial sector of the commune nine of Villavicencio. The results obtained allow a descriptive statistical analysis of the main causes of this problem. The purpose of this article is to generate alternative solutions that help mitigate business desertion and encourage large-scale entrepreneurship. It is estimated that once worktables are created between the government, banks, economic unions, and the business fabric, for the construction of public policies that favor entrepreneurship in the region, the productive sector and society in general will be able to perceive an economic acceleration and a greater welfare state.